2020
DOI: 10.1016/j.chest.2020.05.529
|View full text |Cite
|
Sign up to set email alerts
|

Coronavirus Disease 2019 Infection Among Medical Staff in Wuhan

Abstract: The coronavirus disease 2019 (COVID-19) outbreak in Wuhan, China, has caused considerable infection in health-care workers (HCWs). More than 3,000 cases in 422 involved medical facilities have been reported by the Chinese Center for Disease Control and Prevention (China CDC) as of February 22, 2020; 64% occurred in Wuhan. 1 However, the incidence and patterns of infection in medical staff have not yet been described. Patients and Methods COVID-19 infection rates, models of infection, and clinical characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Most countries have adopted lockdown measures, such as banning social interaction, closing public places and taking isolation measures[ 9 ], which has been proved to be effective in controlling the spread of the virus. However, health care workers at the forefront are at high risk of occupational exposure due to inevitable close contact[ 10 , 11 ]. Therefore, three-grade prevention measures and personal protective equipment are essential for intensivists to avoid further infection in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…Most countries have adopted lockdown measures, such as banning social interaction, closing public places and taking isolation measures[ 9 ], which has been proved to be effective in controlling the spread of the virus. However, health care workers at the forefront are at high risk of occupational exposure due to inevitable close contact[ 10 , 11 ]. Therefore, three-grade prevention measures and personal protective equipment are essential for intensivists to avoid further infection in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…3 During the severe acute respiratory syndrome (SARS) epidemic in 2003, 21% (1706 / 8096) cases were HCWs. 4 In a single-center case series of 138 COVID-19 patients hospitalized in Wuhan, China, in January 2020, 29% (40/138) were HCWs. 5 One report states that about 10 000 HCWs were infected and 74 died in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…For this update, 8 cross-sectional studies ( 3–10 ) were added. Two studies were done in Asia ( 7 , 9 ), 5 were done in Europe ( 4–6 , 8 , 10 ), and 1 was done in Oman ( 3 ).…”
mentioning
confidence: 99%
“…Severe acute respiratory syndrome coronavirus 2 seropositivity, reported in 5 new studies, ranged from 3.2% to 13.2% ( 4–6 , 8 , 10 ). Among HCWs with SARS-CoV-2 infection, 3 studies reported hospitalization rates of 0% to 14.4% ( 3 , 9 , 10 ), and 2 studies reported that 0.7% and 10.2% had severe disease ( 7 , 9 ). In 2 studies, mortality among HCWs with SARS-CoV-2 infection was 0% and 0.7% ( 7 , 9 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation